The language of new media - Manovich, Lev (Leonardo (Series) (Cambridge, Mass.), 2002)
"In this book Lev Manovich offers the first systematic and rigorous theory of new media. He places new media within the histories of visual and media cultures of the last few centuries. He discusses new media's reliance on conventions of old media, such as the rectangular frame and mobile camera, and shows how new media works create the illusion of reality, address the viewer, and represent space. He also analyzes categories and forms unique to new media, such as interface and database."--Book cover.